Robust nested loop control scheme for LCL‐filtered inverter‐based DG unit in grid‐connected and islanded modes. Issue 11 (17th July 2018) - Buduma, Parusharamulu; Panda, Gayadhar
Abstract : The grid feeding and grid forming inverters are important candidates in grid connected and islanded modes (IMs) of microgrid system, respectively. The grid feeding inverter supplies the preset power during grid‐connected mode and the grid forming inverter generates a reference voltage for other distributed generation (DG) interfacing inverters in IM. In such scenario, the proper control of these inverters is an utmost importance. Generally, a nested loop control strategy uses a conventional PI controller for the inner and outer loops of grid feeding and grid forming inverter, but it gives deteriorative performance under parameter uncertainty condition. This study proposes a robust nested loop control scheme with the mixed H ∞ / H 2 optimal controller in the outer voltage control loop and the robust linear quadratic regulator (LQR) state feedback controller in the inner current control loop for the smooth operation of the system in both modes. The simulation and experimental results of the DG unit with proposed control scheme demonstrate good stability and performance robustness under the parameter uncertainty. Also, superior transient and steady‐state performance are confirmed over the conventional controller.